Tongue colour and coating prediction in traditional Chinese medicine based on visible hyperspectral imaging. Issue 12 (18th September 2019) - Zhang, Dong; Zhang, Junhua; Wang, Zheng; Sun, Meijun
Abstract : Tongue diagnosis is an important concept in Traditional Chinese Medicine (TCM). The tongue colour and coating can aid understanding of the body's physiological mechanisms, as well as the pathology of diseases. Existing research has focused on using digital images and tongue colour classification, without considering the other visible bands of information in the tongue. In this study, a visible hyperspectral image system, with an approximate spectral range of 400–1000 nm, was used to predict the tongue colour values and the coating position in TCM, and a stacked autoencoder (SAE) predict model based on spectral–spatial feature was performed to digital the tongue colour space and the coating. The experimental results show the effectiveness of the spectral–spatial feature with SAE model in predicting the CIELAB values of L, a, and coating position, thus the authors provide a new technique for the objective and digitising development of TCM.